2019
DOI: 10.1186/s12891-019-2559-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk for cervical herniated intervertebral disc in dentists: a nationwide population-based study

Abstract: Background Prolonged static postures (PSPs) may predispose dentists to develop cervical herniated intervertebral disc (C-HIVD); however, there is limited evidence supporting this in the literature thus far. We conducted this study to fit the data gap. Methods We conducted a retrospective nationwide population-based study using the Taiwan National Health Insurance Research Database to identify 10,930 dentists, an identical number of age- and sex-matched participants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Therefore, stiff atlanto-occipital joint, represented by low FOC, makes increased mechanical stress downward. This may aggravate degeneration or herniation of the spinal discs [17,21]. The presented case (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Therefore, stiff atlanto-occipital joint, represented by low FOC, makes increased mechanical stress downward. This may aggravate degeneration or herniation of the spinal discs [17,21]. The presented case (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies indicated that pathophysiological changes, such as disc degeneration and disc protrusion, were surprisingly common ndings in young adults with neck pain [16,17]. The course and outcome of CS are highly varied, especially in young patients [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations